DATA ENGINEERING IN MANUFACTURING: ENHANCING SUPPLY CHAIN EFFICIENCY - Prakash Babu Sankuri, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article explores the transformative impact of data engineering on manufacturing and supply chain efficiency. The article examines how advanced data pipeline architectures, real-time processing capabilities, and predictive analytics are revolutionizing traditional manufacturing processes. The article investigates the implementation of dynamic inventory optimization, automated replenishment systems, and quality control mechanisms through AI and machine learning. The article encompasses supply chain transparency, production optimization, and cost reduction strategies while highlighting the crucial role of edge computing integration in modern manufacturing environments. The article demonstrates significant improvements in operational efficiency, maintenance practices, and decision-making capabilities across various manufacturing sectors, providing valuable insights for organizations seeking to enhance their manufacturing operations through data engineering solutions.